The rise and evolution of Korean Christian foreign missions and political interaction - Yong Qian; Yinji Zhao (HTS Teologiese Studies/Theological Studies)
Korea has seen remarkable development into a key worldwide missionary force since the advent of Christianity in the late 19th century. Building upon this context, the objective of this article is to explore the historical and practical consequences of the increase in Korean Christian overseas missionary endeavours and their relationship with politics. The article emphasises the pivotal significance of political elements in the transition from quantitative to qualitative transformations in Korean Christian missionary movements. For this purpose, the study takes a political science approach, methodically examines the historical relationship between Korean Christian foreign missionary activities and politics, and demonstrates how Korean Christianity has evolved from a key influence in the national movement to a significant participant in contemporary politics, encompassing both international and domestic politics. Given the changing political landscape, the overseas missionary efforts of Korean Christianity have emerged as a crucial element of the country’s soft power, serving to protect national interests and propagate its religious beliefs.